CESA5 Is Required for the Synthesis of Cellulose with a Role in Structuring the Adherent Mucilage of Arabidopsis Seeds(1)([C])([W]) - Sullivan, Stuart (American Society of Plant Biologists, 2011)
Imbibed Arabidopsis (Arabidopsis thaliana) seeds are encapsulated by mucilage that is formed of hydrated polysaccharides released from seed coat epidermal cells. The mucilage is structured with water-soluble and adherent layers, with cellulose present uniquely in an inner domain of the latter. Using a reverse-genetic approach to identify the cellulose synthases (CESAs) that produce mucilage cellulose, cesa5 mutants were shown to be required for the correct formation of these layers. Expression of CESA5 in the seed coat was specific to epidermal cells and coincided with the accumulation of mucilage polysaccharides in their apoplast. Analysis of sugar composition showed that although total sugar composition or amounts were unchanged, their partition between layers was different in the mutant, with redistribution from adherent to water-soluble mucilage. The macromolecular characteristics of the water-soluble mucilage were also modified. In accordance with a role for CESA5 in mucilage cellulose synthesis, crystalline cellulose contents were reduced in mutant seeds and birefringent microfibrils were absent from adherent mucilage. Although the mucilage-modified5 mutant showed similar defects to cesa5 in the distribution of sugar components between water-soluble and adherent mucilage, labeling of residual adherent mucilage indicated that cesa5 contained less cellulose and less pectin methyl esterification. Together, the results demonstrate that CESA5 plays a major and essential role in cellulose production in seed mucilage, which is critical for the establishment of mucilage structured in layers and domains.